Corporate Investment and Innovation in the Presence of Competitor Constraints - Grieser, William; Liu, Zack (Review of Financial Studies, 2019)
We study the relation between investment behavior and competitor financial constraints. Using interfirm patent citations and text-based product market similarities to identify intransitive competitor networks, we find that firms increase investment spending, patenting activity, and opportunistic hiring when competitor constraints become more binding. In addition, firms shift their investment composition (product market and patent portfolios) to compete more aggressively with relatively constrained competitors. To mitigate endogeneity concerns, we exploit the 2004 AJCA tax holiday and the 1989 junk bond crisis as exogenous shocks to competitor constraints, and we find similar effects. Received August 11, 2017; editorial decision November 6, 2018 by Editor David Denis. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.